MAGNETOELECTRIC COUPLING MEASUREMENT TECHNIQUES IN MULTIFERROIC MATERIALS - Grotel, Jakub (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
Magnetoelectric multiferroics are solid-state materials which exhibit a coupling between ferroelectric and magnetic orders. This phenomenon is known as the magnetoelectric (ME) effect. Multiferroic materials possess a wide range of potential applications in such fields as metrology, electronics, energy harvesting & conversion, and medicine. Multiferroic research is facing two main challenges. Firstly, scientists are continuously trying to obtain a material with sufficiently strong, room-temperature ME coupling that would enable its commercial application. Secondly, the measurement techniques used in multiferroic research are often problematic to implement in a laboratory setting and fail to yield reproducible results. The aim of the present work is to discuss three most commonly used methods in multiferroic studies; the lock-in technique, the Sawyer-Tower (S-T) circuit and dielectric constant measurements. The paper opens with a general description of multiferroics which is followed by mathematical representation of the ME effect. The main body deals with the description of the aforementioned measurement techniques. The article closes with a conclusion and outlook for future research.